FLOUTING THE MAXIM IN CONVERSATION AT ELLEN DEGENERES SHOW AND THE TONIGHT SHOW STARRING JIMMY FALLON - Maryatul Kipya; Diana Rozelin; Muhammad Beni Saputra (Nazharat: Jurnal Kebudayaan, 2019)
This research analyzes flouting the maxim in conversation at Ellen DeGeneres Show and The Tonight Show Starring Jimmy Fallon, in these talk shows flouting the maxim appears, it causes the speaker and hearer being misunderstanding and not cooperative in the conversation. The aims of this research are to find out the type of flouting the maxim, to know the strategies of flouting the maxim used and to know politeness principle in conversation at Ellen DeGeneres and The Tonight Show Starring Jimmy Fallon.the writer uses the maxim theory by H. Paul Grice (1973) that discusses about types of Flouting the maxim, rhetorical strategies theory by Peter Grundy (1995) that discusses the strategy to flout the maxim, and Politeness Principle Theory by Geoffrey Leech (1983) that discusses the usage and violation of Politeness Principle in the conversation at Ellen DeGeneres and The Tonight Show starring Jimmy Fallon. This research uses the qualitative as the kind of this research, for collecting the data the writer uses the technique of documentation and constant comparative to analyze the data.The result of this research showsthe data based on the formulation of problem. They are: (1), there are four types of flouting the maxim; flouting quantity, flouting quality, flouting relation and flouting manner which have flouted in the conversation at Ellen DeGeneres and The Tonight Show Starring Jimmy Fallon. (2), there are six strategy of flouting the maxim used; tautology, overstatement, understatement, metaphor, rhetorical question, irony. (3), there are seven politeness principle found; tact maxim, modesty maxim, the agreement maxim, the sympathy maxim, the consideration maxim, the generosity maxim, and the praise maxim.